Inovasi Berbasis Konsumen: Merancang Produk Yang Tidak Hanya Baru, Tapi Juga Relevan - Wildan Habibi; Elyanti Rosmanidar (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2025)
A fundamental paradigm shift in product development strategy is observed, moving from technology-driven innovation (technology-push) towards an approach driven by market demand and consumer needs (market-pull), known as Consumer-Driven Innovation. In a saturated and hyper-competitive global market, merely introducing a “new” product no longer guarantees success; deep relevance and inherent value for consumers become the primary distinguishing factors. This analysis explores the key methodologies utilized by leading companies to achieve such relevance, including the leverage of Big Data and Behavioral Analytics to identify consumer pain points and unmet needs, the implementation of a Human-Centered Design approach, and the importance of rapid feedback cycles. Focus is placed on the “Jobs to Be Done” (JTBD) concept, which offers a framework for understanding the underlying consumer motivations behind a purchase. Future economic success depends not solely on the technical capability of companies to innovate, but rather on their strategic intelligence in designing and manufacturing solutions that are authentically relevant to the lives and needs of their target market. This approach is the key to creating long-term value and sustaining global competitiveness